Seyfettin Özege Through Letters and Donation Process of His Library - Yılmaz, Malik (Information World, 2020)
There are now much publications about the life, personality, and works of Mehmet Seyfettin Özege who is best known for his collection donation to Atatürk University. The aim of this study is to give information about the process of letters donation as a special document category, sent by Özege to Atatürk University, and to examine the personality characteristics and perspective about library of the collector. Özege started writing these letters by deciding to make donation and wrote a significant part of his letters to the rectors of Atatürk University at that time. The scope of the letters mostly consists of Özege’s donation requirements and correspondence regarding whether these requests were fulfilled or not. These letters, as primary sources, will help researchers to realize Özege’s approach and sensitivity towards books and libraries. Apart from this, researchers will be provided with information about what Atatürk University (Library) did to organize and to serve the collection as soon as possible and also about all related processes. In the study, document analysis (documentary scanning) method was used to obtain and evaluate the data. Atatürk University Archive was used to obtain the data. The letters sent by Özege to Atatürk University were listed in order of date and those selected for the purpose of the study were examined. Additionally, the processes of the donation took place in the university, the university’s all issues on donated publications, Özege’s personal characteristics and perspective about books and libraries were highlightened, in line with the findings obtained in the study.
Keywords: Mehmet Seyfettin Özege; Atatürk University Library; letters; Seyfettin Özege Collection; book donation